2019
DOI: 10.1038/s41598-019-54956-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking and physical inactivity with MRI derived changes in cardiac function and structure in cardiovascular healthy subjects

Abstract: We aimed to investigate the association of smoking and physical exercise on ventricular function and structure, determined by cardiac magnetic resonance imaging (CMR), in subjects without known cardiovascular diseases. A total of 381 participants (median age 57 years) of the Cooperative Health Research in the Region of Augsburg (KORA) FF4 cohort underwent CMR. The participants’ smoking and sporting habits were measured by a questionnaire. Physical inactivity was associated with a reduction of left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that the level of physical activity [22], smoking [23] and the left ventricular hypertrophy [12,24] affect the right ventricle. It was previously shown that healthy residents of highlands have small left heart and large right ventricle due to exposure to hypoxemia at high altitudes, and these changes did not depend on ethnicity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the level of physical activity [22], smoking [23] and the left ventricular hypertrophy [12,24] affect the right ventricle. It was previously shown that healthy residents of highlands have small left heart and large right ventricle due to exposure to hypoxemia at high altitudes, and these changes did not depend on ethnicity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the practice of smoking was associated with a 70% reduction in aerobic capacity. The deleterious effects of smoking on aerobic fitness are well established by science; however, it should be noted that smoking is also an independent risk factor for cognitive decline [ 26 ] and has important deleterious effects on the cardiac structure and function [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the main analyses, we investigated CMR parameters that were most strongly correlated with CVD risk factors in previous studies of this sample (LV: end-diastolic volume, stroke volume, diastolic myocardial mass, early diastolic filling rate; RV: end-diastolic volume, stroke volume; fat: epicardial, diastolic) [ 14 , 16 18 ].…”
Section: Methodsmentioning
confidence: 99%